bjr
réels : a et b
on a donc :
a + b = -3/10 (1)
a x b = -2/5 (2)
du (1) on a : a = -3/10 - b
le (2) devient : (-3/10 - b) x b = -2/5
on continue avec le (2) :
-3/10b - b² = -2/5
-b² - 3/10b + 2/5 = 0
=> b² + 3/10b - 2/5 = 0
on cherche les racines :
Δ = (3/10)² - 4*1*(-2/5) = 9/100 + 8/5
= 9/100 + 160/100 = 169/100 = (13/10)²
b' = (-3/10 + 13/10) / 2 = 10/10 /2 = 0,5
b'' = (-3/10 - 13/10) / 2 = -16/10 /2 = -0,8
si b = 0,5 => a = -3/10 - 1/2 = -3/10 - 5/10 = -8/10 = -0,8
si b = -0,8 => a = -3/10 - (-0,8) = -0,3 + 0,8 = 0,5